Bright young women - Knoll, Jessica (Marysue Rucci Books, 2023)
"The book opens on a Saturday night in 1978, hours before a soon-to-be-infamous murderer descends upon a Florida sorority house with deadly results. The lives of those who survive, including sorority president and key witness, Pamela Schumacher, are forever changed. Across the country, Tina Cannon is convinced her missing friend was targeted by the man papers refer to as the All-American Sex Killer--and that he's struck again. Determined to find justice, the two join forces as their search for answers leads to a final, shocking confrontation"--